Analisis Potensi Penurunan Muka Tanah Daerah Wisata Alam Aik Bukaq - Syarifatul Ulfah; Adi Susilo (Jurnal Rekayasa Geofisika Indonesia, 2024)
Land movement is one of natural disaster that occurs unexpectedly. So, the mitigation needs to be provided as early as possible to avoid the impact of the disaster. One of the land movements that often occurs is land subsidence. Within this paper aims to analyze the value of land subsidence in the Nature Tourism area of Aik Bukaq. The land movement was estimated from Sentinel 1A image data with starting from the data range for April 2022 – 2024 and processed using the DInSAR (Differential Interferometry Synthetic Aperture Radar) method in SNAP software. The DinSAR method is one of method that often used to analyze the value of land subsidence. ​Because it’s able to record data in any condition. After processing data in SNAP software, land subsidence values ​​were read and mapped at the coordinate points of research area using Google Earth Pro software. Therefor results obtained the average value of land subsidence in last of 2 years (2022 – 2024), from -0,18 cm/year and -0,21 cm/year respectively. With an average of -0,114 cm/year which is included in the very low land subsidence category. However, there is a significant increase of value in the last 2 years, which really needs to be beware as an initial step to mitigate the impacts of land movement disasters. Because at any time it can happen in the Nature Tourism area of Aik Bukaq